Células endoteliais circulantes em diferentes tipos de tratamentos da Anemia Falciforme - Souza, Claudia Regina Lustosa [UNIFESP] (2020)
Sickle cell anemia (SCA) is characterized by anemia and pain due to chronic hemolysis and recurrent episodes of ischemia, respectively. In the presence of hypoxia, the anomalous hemoglobin (Hb), HbS, triggers microvascular occlusion, a phenomenon enhanced by the adhesion of erythrocytes and leukocytes to the vascular endothelium. As a result, vasculopathy and inflammation characteristic of SCA are observed, with the endothelial cell playing an important role. The endothelium is a dynamic, balanced tissue, where the circulation compartment reflects both the lesion and the regeneration of the vascular tree. In this compartment, circulating endothelial cells (CECs) released from vascular injury and progenitor endothelial cells (PECs) involved in vascular regeneration are identified. However, the importance of these cells in SCA and their relationship with the type of treatment still needs further clarification. Objectives: To evaluate the endothelial phenotype of individuals with sickle cell anemia and determine whether the type of treatment influences this manifestation. Casuistic: 45 patients with SCA were analyzed, followed up at the Hemoglobinopathies Outpatient Clinic of Escola Paulista de Medicina (EPM / UNIFESP). According to the treatment, the following groups were distributed: a) SS (N = 11) - steady state without hydroxyurea (HU); b) SS-HU (N = 19) – in use of maximum tolerated dose of HU; c) SS-TF (N = 15) - chronic transfusion regimen. Control group (CN, N = 13) consisting of healthy individuals. Work approved by Ethical Comittee and participants signed an informed consent form. Exclusion criteria: pregnant and puerperal women, vaso-occlusive crisis in the last 3 months, chronic renal failure and active leg ulcer. In the SS and SS-HU groups, those who received red blood cell transfusion in the last 3 months were also excluded. Methods: Laboratory evaluation: complete blood count, hemolysis tests and C-reactive protein (CRP). Identification and quantification of CECs and PECs performed by Flow Cytometry (FACSCantoII®). Results: The SS group had a higher number of CECs (median: 2.73; range: 0 - 20.0) than the CN (0.39; 0 - 4.20) and the SS-TF (0.67 ; 0 - 2.99), p = 0.016 and 0.013 respectively. The SS-HU group showed higher PECs quantification (0; 0 - 6.62) than the SS and SS-TF groups (0; 0 - 0 in both groups), p <0.05. There was no relationship between determination of CECs and clinical manifestations, however patients with priapism showed higher values (2.28; 0.74 - 6.09) than those without this manifestation (0.68; 0 - 20.0) with p = 0.055. There was no significant correlation between PECs data and clinical manifestations. Discussion & Conclusion: Our results corroborate previous studies that associate the increase in CECs with endothelial complications of SCA. The presence of fewer PECs in groups SS and SS-TF when compared to SS-HU group suggests that HU can provide endothelial protection and raises the question of its indication for all SCA patients in order to prevent serious manifestations related to endothelial dysfunction.